First isolation of Cryptococcus gattii molecular type VGII and Cryptococcus neoformans molecular type VNI from environmental sources in the city of Belém, Pará, Brazil - Solange do PSE Costa; Márcia dos S Lazéra; Wallace RA Santos; Bernardina P Morales; Cláudia CF Bezerra; Marília M Nishikawa; Gláucia G Barbosa; Luciana Trilles; José LM do Nascimento; Bodo Wanke (Memorias do Instituto Oswaldo Cruz, 2009)
Cryptococcus neoformans and Cryptococcus gattii are important agents of meningoencephalitis in humans in the city of Belém. This clinical data suggests that the region may be a highly endemic area for the pathogenic Cryptococcus species within the state of Pará (PA), Northern Brazil. Preliminary analysis of 11 environmental samples from the city of Belém showed two positive locations, including a hollow of a kassod tree (Senna siamea) colonized simultaneously by C. gattii molecular type VGII and C. neoformans molecular type VNI, and a birdcage in a commercial aviary positive for C. neoformans, molecular type VNI. This is the first evidence of an environmental occurrence of molecular types VNI and VGII in PA.